The Impact of the Think Pair Share Cooperative Learning Model with Multi-Representation Based Worksheet on Students’ Critical Thinking - Ita Nurussofi; I Ketut Mahardika; Aris Singgih Budiarso (Journal of Science and Science Education, 2022)
This study aimed to see how Think Pair Share (TPS) learning model combined with multi-representation-based student worksheet affected junior high school students' critical thinking abilities and learning outcomes. This type of research is a quasi-experimental design with a non-equivalent control group. The population in this study was all class VII MTsN 4 Banyuwangi (2021/2022). Data collection techniques using test observation, interviews, and documentation. The data analysis technique used a normality test and Independent Sample T-test with the help of SPSS 25 software. Following is the study's finding: (1) The TPS learning paradigm considerably impacts critical thinking skills, as evidenced by the experimental class's average critical thinking score increasing from 22.28 to 58.96; (2) Students in the experimental class form those in the control class in science. The experimental class's average learning outcome is 52, whereas the control class's average is 35.6. TPS learning paradigm has a considerable influence on critical thinking abilities and learning.